The Challenge of the Believing Intellectual - John O. Voll (International Institute of Islamic Thought, 2011)
This paper analyzes the role of Professor al Faruqi as a believing intellectual who contributed toward the development of an alternative model of modernity in which religion plays a definite and contributory role. Alternative modernity is not inevitably secular or nonreligious. This Islamic version of modernity is one amongst the multiple modernities of the globalized world. It puts forth a “modern” knowledge. Professor al Faruqi contributed to this venture through his project called the “Islamization of Knowledge.” In this way, Professor Ismail al-Faruqi illustrates the changing role of believing intellectuals in the second half of the twentieth century.